FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK SAFETY DRIVING PADA PENGEMUDI ROAD TANK PT. PERTAMINA EP ASSET 4 FIELD CEPU - Muthia Ayuningtyas; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Safety driving is a correct way to drive and knowing proper driving technique so will always be safe while driving. PT. Pertamina EP Asset 4 Field Cepu is a company conducting business activities in upstream oil and gas sector. The activity of oil and gas transport use a vehicle called road tank. The aim of this study was to analyze  factors related the safety driving practice of road tank’s driver PT. Pertamina EP Asset 4 Field Cepu. This study used an explanatory research with cross sectional approach. Population of this study was all of road tank’s driver PT. Pertamina EP Asset 4 Field Cepu and the number of sample in this study were 34 respondents. Sampling techniques of this study was total sampling. Data were collected by using a questionnaire. Data were analyzed using rank spearman and chi square test. The result shows that variabels related to the safety driving practice of road tank’s drivier PT Pertamina EP Asset 4 Field Cepu were the vehicle condition (p=0,001),  safety driving training participation (p=0,025),  the route condition (p=0,001), and knowledge (0,044) and variabels unrelated to the safety driving practice of road tank’s drivier PT Pertamina EP Asset 4 Field Cepu were working time (p=0,398), education (p=0,817), and the friends role (p=0,137).